Sensory discriminability of older consumers: Interaction between evaluation method, number of samples, and age-related characteristics - Su Yun Lim; Mi-Ran Kim (Food Research International, 2026)

Suppressing microRNA396 activity enhances regeneration efficiency of viable shoots from cotyledon explants in pepper - Min Jun Shin; Seong Sub Ku; Su-Jin Park; Sang Un Park; Sung Ran Min; Hyun-Soon Kim; Hyo-Jun Lee (Plant Biotechnology Reports, 2026)

Enhanced fumigant toxicity of methyl benzoate and phosphine combination against phosphine-resistant Rhyzopertha dominica (Fabricius) (Coleoptera: Bostrichidae) - Hwal-Su Hwang; Md Munir Mostafiz; Jun-Ran Kim; Bong-Su Kim; Soo-Jung Suh; Jinmo Koo; Kyeong-Yeoll Lee (Journal of Stored Products Research, 2026)

Synergistic toxicity assessment of ethyl formate combined with low-oxygen and cold treatments against the red flour beetle, Tribolium castaneum Herbst - Jae-Ho Ban; Jin-Sung Yoo; Ji-Eun Choi; Jun-Ran Kim; Bong-Su Kim (Journal of Stored Products Research, 2026)

Integrated hydroprocessing and microbial biotransformation of coconut oil to α,ω-diacids - Bashu Dev Pardhe; Il-Ho Choi; Chang Hoon Lee; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Hwabong Jeong; Jongbeom Park; Kyung Taek Heo; et al. (Bioresource Technology, 2025)

Identification and functional analysis of MYB group transcripts in formation and development of rose prickle - Ka Youn Lee; Yae Jin Kim; Chang Ho Ahn; Kyoung Ran Do; Youn Jung Choi; Jae A. Jung; O Hyeon Kwon; Hye Ryun An; So Hyeon Lim; Su Young Lee (Euphytica, 2025)

Transcriptomic insights into detoxification and mitochondrial responses of Tribolium castaneum (Coleoptera: Tenebrionidae) to carbonyl sulfide exposure - Na-Ri Shin; Rashmi Manohar Mahalle; Jun-Ran Kim; Bong-Su Kim; Keon Mook Seong (Journal of Stored Products Research, 2025)

Rocaglamide-A mitigates LPS-induced hepatic inflammation by modulating JNK/AP-1 signaling cascade and ROS production in hepatocytes - Yoon-su Ha; Taek-Kyong Kim; Jun Heo; Jintaek Oh; Seung-Kyoon Kim; Jeongkyu Kim; Jeonghyung Lee; Se-Ran Yang; Seonghwan Hwang; Seung-Jin Kim (Toxicological Research, 2025)

Eco-friendly biocontrol of pine wilt disease: Enhancing tree defense with Bacillus subtilis JCK-1398 for sustainable forest management - Mohamed Mannaa; Ae ran Park; Jungwook Park; Hee Won Jeon; Hyejung Jung; Hyo Seong Jeon; Gil Han; Jin-Cheol Kim; Young-Su Seo (Science of The Total Environment, 2024)

Sea Water Turbidity Variability and Relation to Tides and Environmental Factors in the Korean Coastal Region of the Yellow Sea - Su-Ran Kim; Tae-Sung Kim; Kyung-Ae Park; Jae-Jin Park; Moon-Jin Lee; Do-Seong Byun (Ocean Science Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Insights into tissue accumulation, depletion, and health risk assessment of clopidol in poultry - Wenting Wang; Min-Chul Shin; Sang-Hee Jeong; Jeong-Ran Min; Jong-Su Seo; Jong-Hwan Kim (Food Additives & Contaminants: Part A, 2024)

Correction to: Prediction of strawberry fruit yield based on cultivar-specific growth models in the tunnel-type greenhouse - Jung Su Jo; Dong Sub Kim; Won Jun Jo; Ha Seon Sim; Hye Jin Lee; Yu Hyun Moon; Ui Jeong Woo; Soo Bin Jung; Steven Kim; Xiaoming Mo; Su Ran Ahn; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2023)

Phytosulfokine promotes cell division in protoplast culture and adventitious shoot formation in protoplast-derived calluses of Nicotiana benthamiana - Su Ji Joo; Seung Hee Choi; Eun Yee Jie; Ok Ran Lee; Suk Weon Kim (Plant Biotechnology Reports, 2022)

Prediction of strawberry fruit yield based on cultivar-specific growth models in the tunnel-type greenhouse - Jung Su Jo; Dong Sub Kim; Won Jun Jo; Ha Seon Sim; Hye Jin Lee; Yu Hyun Moon; Ui Jeong Woo; Soo Bin Jung; Steven Kim; Xiaoming Mo; Su Ran Ahn; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2022)
The strawberry growth and fruit yield of five Korean cultivars in the tunnel-type greenhouse predicted using their growth. The number of leaves, petiole length, leaf length and width, crown diameter, and the ratio of red and far-red (RFR) of the five Korean cultivars were measured during the cultivation period. The number of leaves of all cultivars exhibited a similar trend during this period; the plant and petiole length of ‘Maehyang’ were the longest, leaf length exhibited similar trends in all five cultivars except for ‘Jukhyang’, the leaf width of ‘Arihyang’, was the longest, and crown diameter of ‘Keumsil’ was the thickest. The leaf length, crown diameter, and RFR were associated with the fruit yield in the multiple linear regression. When a single model was used to predict the yield of all five cultivars, the correlation between expected yield and actual yield was r = 0.53. When cultivar-specific models were built for the prediction, the correlation increased to r = 0.77. The results indicated that the fruit yield of strawberry cultivars could be better predicted by considering cultivar-specific information, so it may be necessary to consider individual cultivars specifically rather than all cultivars simultaneously.

Ovalbumin and cholera toxin delivery to buccal mucus for immunization using microneedles and comparison of immunological response to transmucosal delivery - Yu-Jeong Oh; Hye-Ran Cha; Su Jin Hwang; Dae-Sung Kim; Yu-Ji Choi; Yun-Seo Kim; Yu-Ra Shin; Thuy Trang Nguyen; Seong-O Choi; Jae Myun Lee; Jung-Hwan Park (Drug Delivery and Translational Research, 2021)

Anti-bacterial effects of components from Sanguisorba officinalis L. on Vibrio vulnificus and their soluble epoxide hydrolase inhibitory activity - Xiang Dong Su; Rui Hong Guo; Seo Young Yang; Young Ho Kim; Young Ran Kim (Natural Product Research, 2019)

The complete genome sequence of apple rootstock virus A, a novel nucleorhabdovirus identified in apple rootstocks - Dasom Baek; Seungmo Lim; Ho-Jong Ju; Hyun-Ran Kim; Su-Heon Lee; Jae Sun Moon (Archives of Virology, 2019)

Acaricidal activity of Asarum heterotropoides root-derived compounds and hydrodistillate constitutes toward Dermanyssus gallinae (Mesostigmata: Dermanyssidae) - Jun-Ran Kim; Haribalan Perumalsamy; Ju-Hee Lee; Young-Joon Ahn; Young Su Lee; Sang-Guie Lee (Experimental and Applied Acarology, 2016)

Complete genome sequence of a novel endornavirus isolated from hot pepper - Seungmo Lim; Kil Hyun Kim; Fumei Zhao; Ran Hee Yoo; Davaajargal Igori; Su-Heon Lee; Jae Sun Moon (Archives of Virology, 2015)

The complete genome sequences of two isolates of cnidium vein yellowing virus, a tentative new member of the family Secoviridae - Ran Hee Yoo; Fumei Zhao; Seungmo Lim; Davaajargal Igori; Sang-Mok Kim; Tae-Jin An; Su-Heon Lee; Jae Sun Moon (Archives of Virology, 2015)

Freezing and Frost Damage of Potato Plants: a Case Study on Growth Recovery, Yield Response, and Quality Changes - Dong Chil Chang; Hwang Bae Sohn; Ji Hong Cho; Ju Sung Im; Yong Ik Jin; Gyeong Ran Do; Su Jeong Kim; Hyun Mook Cho; Yong Beom Lee (Potato Research, 2014)

Molecular characterization of KGH, the first human isolate of rabies virus in Korea - Jun-Sun Park; Chi-Kyeong Kim; Su Yeon Kim; Young Ran Ju (Virus Genes, 2013)

First complete genomic characterization of two tick-borne encephalitis virus isolates obtained from wild rodents in South Korea - Seok-Min Yun; Su Yeon Kim; Young Ran Ju; Myung Guk Han; Young Eui Jeong; Jungsang Ryou (Virus Genes, 2011)

Development of gene-based markers for the Bs2 bacterial spot resistance gene for marker-assisted selection in pepper (Capsicum spp.) - Hai Thi Hong Truong; Ki-Taek Kim; Su Kim; Myoung-Cheol Cho; Hyun-Ran Kim; Jong-Gyu Woo (Horticulture, Environment, and Biotechnology, 2011)

Characterization of a mannose-6-phosphate isomerase from Geobacillus thermodenitrificans that converts monosaccharides - Soo-Jin Yeom; Nam-Hee Kim; Ran-Young Yoon; Hyun-Jung Kwon; Chang-Su Park; Deok-Kun Oh (Biotechnology Letters, 2009)

An atypical soybean leucine-rich repeat receptor-like kinase, GmLRK1, may be involved in the regulation of cell elongation - Sunghan Kim; Su-Jin Kim; Yun-Jeong Shin; Ji-Hye Kang; Mi-Ran Kim; Kyoung Hee Nam; Myeong-Sok Lee; Suk-Ha Lee; Yul-Ho Kim; Soon-Kwan Hong; Desh Pal S. Verma; Jong-Yoon Chun; et al. (Planta, 2009)

Morphological and random amplified polymorphic DNA features in populations ofCeramium kondoi (Rhodophyta) - Kim Sun Ran; Hwan Su Yoon; Sung Min Boo; Sang Gi Paik (Journal of Plant Biology, 1997)